2010
DOI: 10.1021/es1000566
|View full text |Cite
|
Sign up to set email alerts
|

End-User Preferences for and Performance of Competing POU Water Treatment Technologies among the Rural Poor of Kenya

Abstract: Household point-of-use (POU) water treatment technologies targeted at vulnerable populations are microbiologically effective and, in small trials, improve health. We do not understand the factors that influence preference for and adoption of these technologies by target end-users. We cycled 400 rural subsistence farm households in western Kenya through three randomly ordered two-month trials of three POU products: dilute hypochlorite solution, porous ceramic filtration, and a combined flocculant-disinfectant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 15 publications
5
95
0
Order By: Relevance
“…2). PuR removes turbidity, and households with turbid water liked it more; this has not been the case for some previous studies (Albert et al, 2010). Takasa Maji did better than PuR, so it seems that generic packaging did not negatively affect preferences (Figs.…”
Section: User Preferencesmentioning
confidence: 68%
See 3 more Smart Citations
“…2). PuR removes turbidity, and households with turbid water liked it more; this has not been the case for some previous studies (Albert et al, 2010). Takasa Maji did better than PuR, so it seems that generic packaging did not negatively affect preferences (Figs.…”
Section: User Preferencesmentioning
confidence: 68%
“…Following the household water literature, we argue that preferences are an important indicator of what might be adopted and regularly used (Albert et al, 2010). The user preference ranking exercise indicated that boiling (with an efficient stove) and the pot filter (with a storage container) were the most preferred HWTS options, before costs were factored in.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, our percentage declined to 58% during period 2, the Arnold & Colford meta-analysis relied on studies that had a median length of only 30 weeks. A recent study that compared the e↵ectiveness of chlorination with a silver-coated porous ceramic candle element found a mean log reduction value of 1.21 for households provided WaterGuard (a dilute hypochlorite solution) while the ceramic candles provided a log reduction of only 0.91 (Albert et al , 2010). Finally, it is worth noting that if the log reduction values measured in our study were to be improved to 3 or better, it could lead to improved outcomes (Mellor et al , 2013b).…”
Section: Discussionmentioning
confidence: 50%